2016
DOI: 10.1103/physrevlett.117.046801
|View full text |Cite
|
Sign up to set email alerts
|

Fractionally Charged Zero-Energy Single-Particle Excitations in a Driven Fermi Sea

Abstract: A voltage pulse of a Lorentzian shape carrying a half of the flux quantum excites out of a zerotemperature Fermi sea an electron in a mixed state, which looks like a quasi-particle with an effectively fractional charge e/2. A prominent feature of such an excitation is a narrow peak in the energy distribution function laying exactly at the Fermi energy µ. Another spectacular feature is that the distribution function has symmetric tails as above as below µ, which results in a zero energy of an excitation. This s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 56 publications
0
29
0
Order By: Relevance
“…, the nature of half‐integer Lorentzian charge pulses has been studied and it has been shown that they can form remarkable fractionally charged zero‐energy single‐particle excitations states. Separating the half‐leviton into a e/2 charge part and its accompanying neutral electron–hole cloud, showed that half‐levitons and antihalf‐levitons mixed in a semi‐transparent electronic beam‐splitter can elastically annihilate. This property is not shared with ordinary distinguishable electron and hole excitations.…”
Section: Perspectivesmentioning
confidence: 99%
“…, the nature of half‐integer Lorentzian charge pulses has been studied and it has been shown that they can form remarkable fractionally charged zero‐energy single‐particle excitations states. Separating the half‐leviton into a e/2 charge part and its accompanying neutral electron–hole cloud, showed that half‐levitons and antihalf‐levitons mixed in a semi‐transparent electronic beam‐splitter can elastically annihilate. This property is not shared with ordinary distinguishable electron and hole excitations.…”
Section: Perspectivesmentioning
confidence: 99%
“…which cannot exist without the presence of electron-hole excitation. 15 These works demonstrate the possibility of manipulating electron-hole excitation via engineering the temporal profile of the voltage pulse. In contrast, if the thermal transport is concerned, 16-23 the electron-hole excitation are favorable, since they carry a finite amount of energy, while do not affect the average charge transport.…”
Section: Introductionmentioning
confidence: 94%
“…This linear property of the correlation functions can be used, for example, to separate out a single-particle contribution from the multi-particle one, see, for example, Ref. [72]. F.1.2 Single-particle incoming states When the sources emit single particles in a pure state, we have G (1) γ (t 1 ; t 2 ) = Ψ * γ (t 1 )Ψ γ (t 2 ), γ = 1, 2.…”
Section: E Heat Noise In Terms Of the Excess-correlation Matrixmentioning
confidence: 99%